Numerical framework for multi-scale modeling planar DC magnetron sputtering - Tran, Si Bui Quang; Leong, Fong Yew; Hariharaputran, Ramanarayan; Wenjun, Ding; Lai, Po-Yen; Le, Duc Vinh (Vacuum, 2023)
In this study, we propose a numerical framework for multi-scale modeling planar Direct Current (DC) magnetron sputtering for a single alloy target. In the model, we account for electromagnetics, fluid dynamics, discharge chemistry and thermal transport across multiple length scales. Specifically, we employ Lattice Boltzmann Method (LBM) for transport phenomena, Finite Elements Method (FEM) for magnetron discharge transport, and binary collision approximation Monte-Carlo method for sputtering and atomic deposition. Our modeling framework could predict the composition, uniformity, and deposition flux of deposited thin film alloys. Furthermore, the simulation also provides the information of plasma in the chamber such as electron, ion densities, argon ion energy and argon ion flux bombarding on the target. Through parametric analyses, we found that substrate film composition is scaled with both chamber pressure and inverse chamber temperature, although the effect of chamber temperature is considerably marginal under low pressure conditions. We also found that magnetic fields do not influence the film composition, but it significantly affects the substrate deposition flux and film uniformity. Our work provides useful insights to operational heuristics involved in magnetron sputtering and other physical chemical processes. •The modeling framework provides a strong predictor for stoichiometric composition of deposited thin film alloys.•A reduction in substrate radius and substrate-target distance can lead to improved deposition efficiency and film uniformity.•Magnetic fields can significantly affect the substrate deposition flux and film uniformity.•Substrate composition is found to scale with both chamber pressure and inverse temperature.